Effect of Gabapentin on Opioid Requirement in patients undergoing total Abdominal Hysterectomy - Talha Masood, Fatima Buzdar, Tayyaba Tabassum, Muhammad Fareed Azam, Sana Mujahid, Rashida Farooqi (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pain following surgery has an effect on anesthesia and surgical recovery. To improve the benefits and lessen the problems of opioids, combination regimens of non-opioid and opioid medications are used. Objective: The aim of this study was to determine the effect of gabapentin on opioid requirement in patients undergoing total abdominal hysterectomy. Materials and method: The current double blind controlled trial was carried out at the department of anesthesia, Umer Clinic, PKLI and POF hospital from January 2023 to June 2023 after taking permission from the ethical committee of the hospital. A total of 80 individuals of different age groups (ranged 41-61 years) with ASA I and II performing total abdominal hysterectomy were enrolled. These individuals were classified equally in two groups. There are 40 individuals in each of the two groups, Group S (study group, experimental group) & Group C (control group). Two hours before to surgery, 40 patients in Group S got oral gabapentin 1200 mg, while 40 participants in Group C received oral placebo capsules. Both groups received the same anesthetic method. All patients were put under general anesthesia. Following surgery, patients’ pain levels were assessed using the VAS score 1–10. The information above was gathered by the assigned nurse who was blind to the treatment groups. SPSS version 12 was used to process the data. Applying the Student’s t-test was applied to the assess pain score and supplemental nalbuphine requirements. A p-value of < 0.05 was considered significant. Results: 80 individuals were enrolled in this study and were classified in to control and study groups. In both groups, the hemodynamic results remained stable. In both groups, no individuals needed intraoperative rescue analgesics. Following surgery, the gabapentin group’s VAS score at zero, two, eight, sixteen, and twenty-four hours were noticeably lower than the control group’s pain scores. The study group took significantly fewer nalbuphine overall in the first 24 hours following surgery than the control group. The P-value was statistically significant (p< 0.001). Conclusion: The present study concluded that the use of gabapentin greatly lowers intraoperative and postoperative pain. It also minimizes the requirements of opioids in individuals undergoing TAH. Keywords: Gabapentin, TAH, pain, opioids.